Mechanosensory transduction in Drosophila melanogaster - Liang, Xin, 1981- (Springer, 2017)
This book offers an essential introduction for all graduate students and researchers who are working on or interested in mechanotransduction using fruit flies as their model organisms. Designed for accessibility, it follows a simple five-chapter structure, beginning with a general introduction to mechanotransduction in physiology (Chapter 1) and some basic considerations on the principles behind mechanotransduction processes (Chapter 2). In turn, Chapters 3, 4 and 5 focus on mechanoreceptors in Drosophila melanogaster. Chapter 3 explains how the fly's mechanosensitive cells (i.e. mechanoreceptors) contribute to its daily life, while Chapter 4 explores the ultrastructural and mechanical basis for the working mechanisms of various fly mechanoreceptors. Lastly, Chapter 5 elaborates on the structure, function and physiology of mechanosensitive molecules in fly mechanoreceptors. Accordingly, the book provides an overall framework, helping readers understand mechanosensory transduction, from the physiological level to the molecular level.
Keywords: Mechanoreceptors.; Drosophila melanogaster.; elektronické knihy; electronic books